Radar Recognition of Given and Unknown Meteorological Objects - Безрук, В. М.; Хлопов, Г. І. (My University, 2018)
The recognition algorithms of given and unknown meteorological objects based of autoregressive model of the intensity fluctuations of the reflected signals is proposed. The experimental study of the recognition efficiency meteorological objects are presented with using real reflected signals from a weather radar.
Keywords: Meteorological Object; Reflected Signal; Radar Recognition